2019
DOI: 10.1039/c9fo00578a
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum basilicum var. purpurascens leaves (red rubin basil): a source of bioactive compounds and natural pigments for the food industry

Abstract: Ocimum basilicum var. purpurascens leaves are a rich source of bioactive compounds with antimicrobial activity, which could be considered as an excellent ingredient for the food industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
10
10
2
1
Order By: Relevance
“…The highest concentrations of total free sugars were consistently observed in plants fertigated with the highest level of N input. Except for the absence of trehalose, these findings are in agreement with the ones of previous reports [ 30 , 32 ] and suggest that, in all the tested genotypes, the higher levels of N input are associated with enhanced content of total free sugars.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The highest concentrations of total free sugars were consistently observed in plants fertigated with the highest level of N input. Except for the absence of trehalose, these findings are in agreement with the ones of previous reports [ 30 , 32 ] and suggest that, in all the tested genotypes, the higher levels of N input are associated with enhanced content of total free sugars.…”
Section: Resultssupporting
confidence: 93%
“…The energetic value ranging from 351 to 362 kcal/100 g was influenced by both genotype and N input but with no consistent trends being observed. In agreement with previous studies that examined the nutritional value of basil leaves, in this study protein and carbohydrates were the major macronutrients [ 30 , 31 ], although higher levels of proteins were observed in this study in plants nourished with higher levels of N. Examining the nutritional value of dry green basil, Pereira et al [ 32 ] observed similar levels of ash, but substantially higher levels of carbohydrates and lower levels of proteins compared to the present study. Such differences may be associated with different drying methods [ 33 ], different environmental conditions, and particularly to a lower level of N supply during cultivation and to genotypic differences [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations